Effect of different liquids on APC flash-free ceramic bracket's color stability, shear bond strength, and slot surface roughness - Canbaz Çevik Şeyda; Camcı Hasan; Aslantaş Kubilay (Sciendo, 2022)
The aim of this in vitro study was to evaluate the effect of thermal aging and five different discolouring solutions on the shear bond strength (SBS), discoloration, and slot surface roughness (SSR) of Flash-Free ceramic brackets.